Análisis del ahorro de consumo energético implementando domótica en viviendas urbanas - Manzano Ronquillo, Andrés Iván (2025)
This research focuses on the study of the impact of the implementation of home automation systems in urban homes to save energy consumption. Home automation, understood as the automation of home processes through the integration of information and communication technologies, has emerged as a promising solution to improve energy efficiency in the residential sector. The main objective of this study is to analyze the effect of home automation in reducing energy consumption in urban homes, evaluating both the performance of home automation devices and the behavior of users. To achieve this objective, a comprehensive review of the literature related to home automation and energy efficiency was carried out, as well as a field study that included the installation of home automation systems in selected homes and continuous monitoring of energy consumption............